Bewitching women, pious men : gender and body politics in Southeast Asia - Ong, Aihwa; Peletz, Michael G. (University of California Press, 1995)
This impressive array of essays considers the contingent and shifting meanings of gender and the body in contemporary Southeast Asia. By analyzing femininity and masculinity as fluid processes rather than social or biological givens, the authors provide new ways of understanding how gender intersects with local, national, and transnational forms of knowledge and power. Contributors cut across disciplinary boundaries and draw on fresh fieldwork and textual analysis, including newspaper accounts, radio reports, and feminist writing. Their subjects range widely: the writings of feminist Filipinas; Thai stories of widow ghosts; eye-witness accounts of a beheading; narratives of bewitching genitals, recalcitrant husbands, and market women as femmes fatales. Geographically, the essays cover Singapore, Indonesia, Malaysia, Thailand, and the Philippines. The essays bring to this region the theoretical insights of gender theory, political economy, and cultural studies. Gender and other forms of inequality and difference emerge as changing systems of symbols and meanings. Bodies are explored as sites of political, economic, and cultural transformation. The issues raised in these pages make important connections between behavior, bodies, domination, and resistance in this dynamic and vibrant region.